COVID-19 and global food security Two years later - McDermott, John F. M. 1932-; Swinnen, Johan F. M. 1962- (International Food Policy Research Institute (IFPRI), 2022)
Two years after the onset of the COVID-19 pandemic, the health, economic, and social disruptions caused by this global crisis continue to evolve. The impacts of the pandemic are likely to endure for years to come, with poor, marginalized, and vulnerable groups the most affected. In COVID-19 & Global Food Security: Two Years Later, the editors bring together contributions from new IFPRI research, blogs, and the CGIAR COVID-19 Hub to examine the pandemic’s effects on poverty, food security, nutrition, and health around the world. This volume presents key lessons learned on food security and food system resilience in 2020 and 2021 and assesses the effectiveness of policy responses to the crisis. Looking forward, the authors consider how the pandemic experience can inform both recovery and longer-term efforts to build more resilient food systems.
Keywords: COVID-19; Ernährungssicherung